Lateral‐Polarity Structure of AlGaN Quantum Wells: A Promising Approach to Enhancing the Ultraviolet Luminescence. (8th June 2018) - Guo, Wei; Sun, Haiding; Torre, Bruno; Li, Junmei; Sheikhi, Moheb; Jiang, Jiean; Li, Hongwei; Guo, Shiping; Li, Kuang‐Hui; Lin, Ronghui; Giugni, Andrea; Di Fabrizio, Enzo; et al.
Abstract: Aluminum‐gallium‐nitride alloys (Al x Ga1– x N, 0 ≤ x ≤ 1) can emit light covering the ultraviolet spectrum from 210 to 360 nm. However, these emitters have not fulfilled their full promise to replace the toxic and fragile mercury UV lamps due to their low efficiencies. This study demonstrates a promising approach to enhancing the luminescence efficiency of AlGaN multiple quantum wells (MQWs) via the introduction of a lateral‐polarity structure (LPS) comprising both III and N‐polar domains. The enhanced luminescence in LPS is attributed to the surface roughening, and compositional inhomogeneities in the N‐polar domain. The space‐resolved internal quantum efficiency (IQE) mapping shows a higher relative IQE in N‐polar domains and near inversion domain boundaries, providing strong evidence of enhanced radiative recombination efficiency in the LPS. These experimental observations are in good agreement with the theoretical calculations, where both lateral and vertical band diagrams are investigated. This work suggests that the introduction of the LPS in AlGaN‐based MQWs can provide unprecedented tunability in achieving higher luminescence performance in the development of solid state light sources. Abstract : The micro‐photoluminescence (µ‐PL) mapping of the lateral‐polarity structure samples with a color bar (left) represents the integrated emission intensity from multiple AlGaN quantum wells. N‐polar wells shows higher PL intensity than III‐polar wells. Right: Atomic resolution scanning transmission electron microscopy images in the N‐polar and III‐polar domains, where polarity can be clearly identified.